A hydraulic track drive systems resistive force simulation: Considerations for system electrification - Hugh Coyle; Charles Young; Nicola Anderson; Lee Johnston; Robert Gilmour (Results in Engineering)
An overview of hydraulic track drive systems employed in mobile rock crushers for the mining industry is provided. A mathematical model was developed to analyse thrust and resistive forces experienced during typical machine operations, including flat-plane tracking, incline climbing, and pivot turning. The model provides a basis for assessing power demands required to transition from hydraulic to electric drive systems by quantifying relevant resistive forces involved. Simulink simulations of the track loading, transverse and longitudinal resistive forces, and frictional forces were performed to evaluate system performance under various operational conditions. Results show that incline tracking climbing a slope generate significantly higher resistive forces than straight tracking or pivot turning tracking. This study addresses the challenges of electrifying large-scale off-road machinery by providing insights into the operational demands of the hydraulic system. The findings offer a foundation for subsequent research into electric alternatives that can deliver comparable power densities, improve energy efficiency, and reduce emissions. Potential areas for further investigation include battery optimisation, advancements in electric motor technology, and hybrid solutions that bridge hydraulic and fully electric systems.